FACTORS INFLUENCING REPURCHASE INTENTION TOWARD DAIRY PRODUCTS IN GENERATION Y IN BANGKOK, THAILAND - Klaiklung, Jakkarin; Nuangjamnong, Chompu; Phengpis, Supaporn (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2022)
The study aims to determine the effect of purchase intention in dairy products in generation Y consumers. Attitude, brand loyalty, perceived value, health consciousness, subjective norm, and purchase intention are investigated in the study. The sample (384 respondents) was collected from an online survey using a non-probability sampling method by using convenience sampling technique and snowball sampling technique. The data were analyzed by descriptive analysis, simple linear regression, and multiple linear regression to examine the hypotheses with a five-point Likert scale analysis. The study revealed that attitude, brand loyalty, perceived value, and subjective norm significantly influence purchase intention. Health consciousness has a significant influence on attitude. The finding found that perceived value and attitude are the key factors that impact customer purchase intention. Additionally, the study proposes that to increase customer purchase intention is to understand the attitude and perceived value of generation Y customers. The study’s weakness is the small sample size, and the sample size is in Bangkok, Thailand. In conclusion, form research may not be like other locations and does not represent Thai customers.